Issues in the sustainability of products designed for multi-lifecycle - Dunmade, Israel (International Journal of Engineering and Technology, 2014)
Design for multi-lifecycle (DFML) is a sustainable design approach that seeks to maximize the utility of resources used in developing a product by incorporating features that enable the elongation of the techno-economic service life of that product at the design stage. The goal of DFML is “indefinite” use of the resources invested/embodied in a product without compromising its economic value, technological soundness and socio-cultural acceptability. However, there is a limit to how many times a product designed for multi-lifecycle can be cycled. The aim of this research is to identify issues affecting how many times products designed for multi-lifecycle could be cycled. Another goal of this study is to articulate how the understanding of these issues can be utilized in improving product design for multi-lifecycle. This study is based on intensive literature survey and on over twenty years’ experience in conventional- and in sustainable design and development of agri-food machinery. From the study we learned that the sustainability of products and equipment designed for multi-lifecycle depends, among other things, on the durability of the core components, the required performance standard, resource consumption tipping point, economic advantage eradication point, changes in consumer taste, and regulatory changes. It means that the number of times that resources invested in a product designed for multi-lifecycles can be cycled is increasable by improving the durability of the structure and core components of the product. It also means that designers would be able to improve the sustainability of machinery designed for multi-lifecycles by incorporating features that facilitate easy reconfiguration and upgrading of the product at reasonable cost as consumer taste and regulations changes.   Keywords: Design for multi-lifecycle, design for environment, sustainable design, sustainability, Eco design.